(untitled) (Delito y Sociedad, 2022)
The objective of this article is to reconstruct the different social science analyses of criminal procedure reforms in Latin America between the end of the twentieth century and the beginning of the twenty-first century. The review of these analyses will allow us to know which aspects of these reforms were explored by those who carried out these studies. The first section will focus on the evolution of these reforms over time. The second section, focused on the organizational dimension, will explore research on the incorporation of managerialism in reformed criminal procedure systems. Finally, we will reflect about the different actors who played a significant role in these processes. The purpose of identifying these analytical axes is, on the one hand, to outline a state of the art regarding this issue by presenting aspects common to these processes in the Latin American region, as well as certain particularities of these processes. On the other hand, this paper aims to make a contribution to those interested in reflecting on the design of new criminal justice systems in cases where their studies have focused more on their implementation than on their reconfiguration.